Nabi Muhammad saw. (Pemimpin Agama dan Kepala Pemerintahan) - M. Dahlan (Rihlah : Jurnal Sejarah dan Kebudayaan, 2018)
This article aimed to know about the process of preaching of the Prophet Muhammad saw. in spreading Islam, and the leadership of the Prophet Muhammad saw. as the leader of the religion and nation. The first principle is the construction of the Masjid, the second is the Ukhuwwah Islamiyyah, the third is the relationship of friendship among other parties that are Muslims.The greatest success of Prophet Muhammad is able to become the leader of the country and religion which has laid on the foundations of politics in the state of life and with it has become the origin of the spread of Islam until it is able to master 2/3 of the world and become the largest religion nowadays.The realization of the Medina Charter is evidence of the nature of the Prophet Muhammad's vision. He not only emphasized Muslims, but he also accommodated the interests of the Jews and united the two peoples under his leadership. The Prophet Muhammad saw. succeeded in creating unity, as well as brotherhood between the Muhajirin and Anshar. Among the Anshar, Prophet Muhammad saw.is admitted to have recaptured the interconnected relations that had always been hostile. Tujuan tulisan ini adalah untuk mengetahui: (1) bagaimana proses dakwah Nabi Muhammad saw. dalam menyebarkan agama Islam, (2) bagaimana kepemimpinan Nabi Muhammad saw. sebagai pemimpin Agama dan pemimpin negara.Dalam rangka memperkokoh masyarakat dan negara baru itu, ia segera meletakkan dasar-dasar kehidupan bermasyarakat. Dasar pertama, pembangunan masjid, Dasar kedua, adalah ukhuwwah islamiyyah, Dasar ketiga, hubungan persahabatan dengan pihak-pihak lain yang beragama Islam.Kesuksesan terbesar Nabi Muhammad adalah mampu menjadi pemimpin negara dan (sekaligus agama) yang telah meletakkan dasar-dasar politik dalam kehidupan bernegara dan dengan hal tersebut telah menjadi cikal bakan tersebarnya agama Islam hingga mampu menguasai 2/3 dunia dan menjadi agama terbesar hingga sekarang. Terwujudnya Piagam Madinah merupakan bukti sifat kenegarawan Nabi Muhammad saw. Beliau tidak hanya mementingkan umat Islam, tapi juga mengakomodasi kepentingan orang Yahudi dan mempersatukan kedua umat seumpun ini di bawah kepemimpinannya. Bagi umat Islam Nabi Muhammad saw. berhasil menciptakan persatuan dan kesatuan, serta persaudaraan antara kaum Muhajirin dan Anshar. Di kalangan kaum Anshar Nabi diakui telah merekat kembali hubungan antarsuku yang sebelumnya selalu bermusuhan.